Cancer schmancer - Drescher, Fran. (New York, NY : Warner Books, 2002)
The actress-comedian tells of her struggle to get her cancer diagnosed and treated
Keywords: Drescher, Fran; Actors -- United States -- Biography; Cancer -- Patients -- Biography